Impacts of adding FeSO4 and biochar on nitrogen loss, bacterial community and related functional genes during cattle manure composting - Liu, Zhuangzhuang; Yan, Zhiwei; Liu, Gang; Wang, Xinyu; Fang, Jun (Bioresource technology, 2023)
•The addition of biochar and FeSO4 reduce NH3 and N2O emissions by 52.4 and 35.6%.•The addition of biochar and FeSO4 increased the abundance of amoA and narG.•Biochar and FeSO4 addition mitigate nitrogen loss by affecting the nitrogen flux. This study investigated the impacts of adding FeSO4 and biochar to cattle manure and rice straw composts on functional genes controlling nitrogen loss, bacterial community, nitrification, and denitrification. Four treatments were established, including a control group (CP), and CP mixtures that included 4% biochar (TG1), 4% FeSO4 (TG2), or 2% FeSO4 and 2% biochar (TG3). Compared to CP, TG1–3 had a lower total nitrogen loss rate, and TG3 resulted in reduced NH3 (52.4%) and N2O (35.6%) emissions to mitigate nitrogen loss. The abundance of amoA and narG gene in TG3 was higher than in the other groups, and TG3 was beneficial to the growth of Proteobacteria and Actinobacteria. According to redundancy and Pearson analysis, TG3 had a positive effect on the nitrification process by increasing the abundance of amoA and narG. Thus, biochar and FeSO4 addition mitigate nitrogen loss by regulating the nitrification processes.